Assessing Aeolian Sand Potential in Ain Sefra Region - Southwestern of Algeria - Bouarfa, Said; Youb, Okkacha; Khaouani, B.; Berrabah, D.; Djoudi, W. (Technium Social Sciences Journal, 2022)
Ain Sefra is a semi-arid area located in south-western Algeria carried out by sand barring, which has made any development in the area impossible. Thus, to understand this phenomenon, it is useful to estimate the displacement of the quantity of sand and the directions of the effective winds during 30 years (1985-2015) to quantify the phenomenon of silting and categorize the danger. Using the method of Fryberger, anemometric (wind) data from meteorological stations were analyzed to examine the potential for sand drift potential (DP) at Ain Sefra between 1985 and 2015. The objective is to identify the hazard level by estimating the sand displacement and effective wind directions over 30 years (1985-2015). The resulting (potential displacement) DP and directional wind variability are estimated and discussed. The average annual sand DP is expected to be 222VU (vector units). These figures have led to the classification of the Ain Sefra location as a wind environment with intermediate energy levels (medium energy wind environment) (Fryberger and Dean 1979). It is determined that the drift potential is 76 with a migration coefficient of 0.3 and that the area has a medium classification. It is also shown that the complex system of wind erosion and its interrelationship with other components are in play. The sand drift potential environment varies greatly from location to location, and 80% of the resulting annual PDR occurs during the fall season from March to June. In addition, effective winds often blow from the southwest to the northeast at an angle of 234°. In addition, the sand can be in different directions, leading it to drift. We should also mention that the directional variability is also quite high